The role of United States identity in adjustment among Veterans. Issue 6 (1st November 2020) - Meca, Alan; Park, HyeJung; Higgins, Jennise; Hamrick, Hannah; Webb, Taylor; Davies, Rachel; Golembiewski, Leeanna; Bravo, Adrian J.; Kelley, Michelle L.
ABSTRACT: Given over 2.77 million US service members have been deployed in the past 20 years and the intense process of reintegration to civilian life, understanding factors that contribute to Veterans' mental health and substance use is critical. This study sought to understand the effects of US identity exploration, US identity commitment, US identity affirmation, and US identity centrality on substance use and symptoms of depression and anxiety. The sample consisted of 195 US military Veterans ( n = 184, 53.3% women; 73.3% White; Mage = 35.12 years, SD = 9.60 years). Bivariate correlations indicated US identity affirmation was negatively associated with substance use and symptoms of depression and anxiety whereas US identity centrality was positively correlated with alcohol use. Utilizing structural equation model, US identity affirmation and US identity centrality were, respectively, negatively and positively associated with alcohol use, substance use, and symptoms of depression and anxiety. Partially consistent with our hypothesis, US identity exploration was positively associated with symptoms of anxiety. In contrast to our hypothesis, US identity commitment was not significantly associated with any outcome. Results are discussed in terms of important directions for identity research in the transition to civilian life.